2018
DOI: 10.7861/clinmedicine.18-3-201
|View full text |Cite
|
Sign up to set email alerts
|

Gardening for health: a regular dose of gardening

Abstract: There is increasing evidence that exposure to plants and green space, and particularly to gardening, is beneficial to mental and physical health, and so could reduce the pressure on NHS services. Health professionals should therefore encourage their patients to make use of green space and to work in gardens, and should pressure local authorities to increase open spaces and the number of trees, thus also helping to counteract air pollution and climate change.There is anxiety that the NHS cannot cope now and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 43 publications
3
32
0
5
Order By: Relevance
“…Considering this, the four horticultural activities in this study had a relaxing effect on the elderly. Moreover, previous studies showed that blood pressure is significantly lower in the horticultural therapy program [ 27 , 51 ]. However, systolic and diastolic blood pressure were not significantly lower after every activity in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, the four horticultural activities in this study had a relaxing effect on the elderly. Moreover, previous studies showed that blood pressure is significantly lower in the horticultural therapy program [ 27 , 51 ]. However, systolic and diastolic blood pressure were not significantly lower after every activity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, systolic and diastolic blood pressure were not significantly lower after every activity in this study. It might be that previous studies were mostly long-term programs which could explain the tendency for the blood pressure to decrease [ 16 , 27 , 51 ]. This study mainly focused on relatively short-term activities, so there was no significant decrease in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In the eight municipalities, the median of farm surface per owner was 3.70 hectares (rank 2.06 Castelló de la Plana, 9.97 Benicarló). The health effects of gardening have been indicated and Benicarló has a high agricultural occupation percentage [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In scholarly accounts concerned with 'green exercise' (Pretty et al 2007), for instance, nature is said to be beneficial when it is 'directly experienced' by (human) exercisers, that is, when people make a positive decision to go to places where there is green nature. Equally important, according to these researchers, is the 'incidental' physical activity whereupon exercise is secondary to other motives, such as commuting via bicycle through woodland environments or raising ones heartrate through gardening (Thompson 2018). In addition, Coon et al (2011) describe the mental health benefits that can be accrued through one's exposure to views of nature, whilst Yeh et al (2016) analyse the supposedly synergistic relationships between emotional wellbeing and 'green' physical activity.…”
Section: Nature-based Leisurementioning
confidence: 99%